Applications of SNAP‐tag technology in skin cancer therapy. Issue 2 (8th January 2019) - Padayachee, Eden Rebecca; Adeola, Henry Ademola; Van Wyk, Jennifer Catherine; Nsole Biteghe, Fleury Augustine; Chetty, Shivan; Khumalo, Nonhlanhla Patience; Barth, Stefan
Abstract: Background: Cancer treatment in the 21st century has seen immense advances in optical imaging and immunotherapy. Significant progress has been made in the bioengineering and production of immunoconjugates to achieve the goal of specifically targeting tumors. Discussion: In the 21st century, antibody drug conjugates (ADCs) have been the focus of immunotherapeutic strategies in cancer. ADCs combine the unique targeting of monoclonal antibodies (mAbs) with the cancer killing ability of cytotoxic drugs. However, due to random conjugation methods of drug to antibody, ADCs are associated with poor antigen specificity and low cytotoxicity, resulting in a drug to antibody ratio (DAR) >1. This means that the cytotoxic drugs in ADCs are conjugated randomly to antibodies, by cysteine or lysine residues. This generates heterogeneous ADC populations with 0 to 8 drugs per an antibody, each with distinct pharmacokinetic, efficacy, and toxicity properties. Additionally, heterogeneity is created not only by different antibody to ligand ratios but also by different sites of conjugation. Hence, much effort has been made to find and establish antibody conjugation strategies that enable us to better control stoichiometry and site‐specificity. This includes utilizing protein self‐labeling tags as fusion partners to the original protein. Site‐specific conjugation is a significant characteristic of these engineered proteins. SNAP‐tag is one such engineered self‐labeling protein tag shown to have promising potential in cancer treatment. The SNAP‐tag is fused to an antibody of choice and covalently reacts specifically in a 1:1 ratio with benzylguanine (BG) substrates, eg, fluorophores or photosensitizers, to target skin cancer. This makes SNAP‐tag a versatile technique in optical imaging and photoimmunotherapy of skin cancer. Conclusion: SNAP‐tag technology has the potential to contribute greatly to a broad range of molecular oncological applications because it combines efficacious tumor targeting, minimized local and systemic toxicity, and noninvasive assessment of diagnostic/prognostic molecular biomarkers of cancer.